The Influence of Social Marketing Media and Digital Influencers on Fashion Purchase Decisions through Customer Reviews on the Shopee Marketplace - Verawaty Verawaty; Yayu Pratiwi Seran (Jurnal Economic Resource, 2023)
The purpose of this study is to determine and analyze the influence of social media marketing and digital influencers on customer reviews and fashion purchase decisions. To find out and analyze the influence of customer reviews on purchase decisions on the Shopee Marketplace, to find out and analyze the influence of social media marketing and digital influencers on purchase decisions through customer reviews on the Shopee Marketplace. Data collection techniques through the distribution of questionnaires with data analysis techniques using the semPls 3.2.9 method. The results showed that social media marketing has a positive and significant effect on customer reviews, digital influencers have a positive and significant effect on customer reviews, social media marketing has a positive and significant effect on purchasing decisions, digital influencers have a positive and significant effect on purchase decisions, customer reviews have a positive and significant effect on purchase decisions, social media marketing has a significant effect Regarding Purchasing Decisions Through Customer Reviews, Digital Influencers Have a Significant Influence on Purchasing Decisions Through Shopee Market Place Customer Reviews.